2013
DOI: 10.1186/1476-511x-12-181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the n-6/n-3 polyunsaturated fatty acids ratio on postprandial metabolism in hypertriacylglycerolemia patients

Abstract: BackgroundAtherosclerosis is a postprandial phenomenon. The balanced n-6/n-3 PUFA ratio contributing to the prevention of atherosclerosis has been well shown, but the effect of the ratio on postprandial metabolism has not been fully investigated. The aim of this study was to investigate the effects of the n-6/n-3 PUFAs ratio on postprandial metabolism in hypertriacylglycerolemia patients, comparing them to healthy controls.MethodsTest meals with 0.97 (high n-3) and 8.80 (low n-3) n-6/n-3 PUFAs ratio were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…We did not observe any effect of LC n -3 FA intake on postprandial TAG levels. Studies in normo- and hypertriacylglycerolaemic subjects have shown that regular consumption of LC n -3 FA reduces postprandial TAG levels ( 37 39 ) ; however, decreases in postprandial TAG levels have not been observed in acute studies of normotriacylglycerolaemic subjects ( 3 , 31 , 40 ) . The stable fish consumption (≤2 meals/week) among some of the participants over the last 4 months prior to inclusion and throughout the study period may have influenced the postprandial TAG results in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any effect of LC n -3 FA intake on postprandial TAG levels. Studies in normo- and hypertriacylglycerolaemic subjects have shown that regular consumption of LC n -3 FA reduces postprandial TAG levels ( 37 39 ) ; however, decreases in postprandial TAG levels have not been observed in acute studies of normotriacylglycerolaemic subjects ( 3 , 31 , 40 ) . The stable fish consumption (≤2 meals/week) among some of the participants over the last 4 months prior to inclusion and throughout the study period may have influenced the postprandial TAG results in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A more plausible explanation is that high carbohydrate digestion and absorption interferes with lipid utilization as occurs in humans: when the content of dietary carbohydrate is elevated above the level typically consumed, blood concentrations of triglycerides rise even with low-fat diets. This phenomenon is known as carbohydrate-induced hypertriglyceridemia, and is still poorly understood but assumed to be due to increased lipogenesis in liver and limited clearance from blood of both triglycerides [93] and glucose [94] . Postprandial hypertriglyceridemia in humans is also a rare hereditable disorder.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely for n-3 PUFA to need more than 8 h to exert beneficial effects in subjects with an impaired lipid metabolism [ 35 ]. Amount and type of dietary fatty acids can influence postprandial response [ 38 ]. Therefore, an imbalance in the n-3/n-6 fatty acids ratio could modulate postprandial response with more pronounced effects in insulin resistant subjects, such as NAFLD patients.…”
Section: Discussionmentioning
confidence: 99%